2020
DOI: 10.3390/su12051730
|View full text |Cite
|
Sign up to set email alerts
|

Telecoupling of the Trade of Donkey-Hides between Botswana and China: Challenges and Opportunities

Abstract: International trade has become a major threat to biodiversity in the telecoupled world. The literature on biodiversity loss mostly concentrates on wild species; however, the increasing loss of and demand for domesticated species are overlooked. Donkeys are decreasing in many countries because of economic development, urbanization, and increased demand for donkey hides in China. The donkey population in Africa has rapidly declined recently due to supplying China with donkey hides for the production of highly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The participants stated that there is lack of veterinary services to treat donkeys that are sick. This is line with the findings of Matlhola and Chen (2020), which found that diseases are among the factors that reduce the population of donkeys in developing countries where drugs and veterinary services are scarce or non-existent.…”
Section: Discussion Of Major Findingssupporting
confidence: 91%
“…The participants stated that there is lack of veterinary services to treat donkeys that are sick. This is line with the findings of Matlhola and Chen (2020), which found that diseases are among the factors that reduce the population of donkeys in developing countries where drugs and veterinary services are scarce or non-existent.…”
Section: Discussion Of Major Findingssupporting
confidence: 91%
“…There is no one literature relating to donkeys. Academic papers relating to donkeys include intermediate transport [5][6][7], draught animal power [8][9][10], the clinical veterinary, health and welfare disciplines [11][12][13][14] and, increasingly donkey commodities [15][16][17][18][19]. There are also a number of papers specifically about donkeys in Ghana, including transport [20], draught animal power [21,22], gender [5,7,10], livelihoods Ghana who depend on them for their livelihood, donkeys, both alive and dead, are highly valuable even if not of particular significance to Ghana's economy overall (Fig 1).…”
Section: Introductionmentioning
confidence: 99%
“…Maiara estimated that “people do hire the services of my donkey to carry their stuff, but is not all the time”. She potentially earns an additional ~520–1040 GH¢ (~£72.80–145.60) per annum through hiring out her donkey, although as she points out this “is just a little amount because it’s my friends and relatives who beg the services of my donkeys and wouldn’t pay anything to me” [ 2 , 10 , 22 , 23 ]. This compares to Kahiau’s £6.48 for each load his donkeys carry for selling “speculatively”.…”
Section: Resultsmentioning
confidence: 99%
“…As well as the clinical veterinary, health and welfare literatures [ 2 , 3 , 4 , 5 , 6 ] these include draught animal power (DAP), traction and transport [ 6 , 7 , 8 , 9 ], donkeys and livelihoods [ 8 , 9 , 10 , 11 , 12 ], donkey commodities [ 13 , 14 , 15 , 16 ] and donkeys and gender [ 8 , 17 , 18 , 19 , 20 , 21 ]. There is also a growing literature on the increasing demand for donkey hides, a key constituent of a traditional Chinese medicine (TCM) called e’jiao [ 3 , 16 , 18 , 22 , 23 , 24 , 25 , 26 ]. However, in comparison to other economically important species in Majority World agricultural production, donkeys have been under-researched and under-valued.…”
Section: Introductionmentioning
confidence: 99%